2015
DOI: 10.2196/mededu.4267
|View full text |Cite
|
Sign up to set email alerts
|

Information-Seeking Behaviors of Medical Students: A Cross-Sectional Web-Based Survey

Abstract: BackgroundMedical students face an information-rich environment in which retrieval and appraisal strategies are increasingly important.ObjectiveTo describe medical students’ current pattern of health information resource use and characterize their experience of instruction on information search and appraisal.MethodsWe conducted a cross-sectional web-based survey of students registered in the four-year MD Program at Dalhousie University (Halifax, Nova Scotia, and Saint John, New Brunswick, sites), Canada. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 36 publications
3
33
0
2
Order By: Relevance
“…Our study included students from different educational levels ranging from high school to post-graduate students. The vast majority of previous studies on use of internet as a health information source among students included under-graduate university students (Osei Asibey, Agyemang, & Boakye Dankwah, 2017;Albarrak, 2016;O'Carroll, 2015;Aldebasi & Ahmed, 2013;Horgan & Sweeney, 2012;Mahmood et al, 2016;Percheski & Hargittai, 2011). Educational level of students might play a central role on health information seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study included students from different educational levels ranging from high school to post-graduate students. The vast majority of previous studies on use of internet as a health information source among students included under-graduate university students (Osei Asibey, Agyemang, & Boakye Dankwah, 2017;Albarrak, 2016;O'Carroll, 2015;Aldebasi & Ahmed, 2013;Horgan & Sweeney, 2012;Mahmood et al, 2016;Percheski & Hargittai, 2011). Educational level of students might play a central role on health information seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Most young adults are able to search electronic sources for health information and to use these for decision making (Stellefson et al, 2011;Stellefeson et al, 2012;Britt et al, 2017;Bakarman, 2017), and internet is becoming a major source of health information for the new generation (Tao, 2017). Several studies examined students' online habits and their use of internet as a source for health information (Osei Asibey, Agyemang, & Boakye Dankwah, 2017;Albarrak et al, 2016;O'Carroll, 2015;Aldebasi & Ahmed, 2013;Schwartz, 2016;Horgan & Sweeney, 2012;Percheski, 2011;Bensley et al, 2014). A cross-sectional study conducted in 3 universities in Ghana and included 650 students (Osei Asibey, Agyemang, & Boakye Dankwah, 2017), reported that 67.7% of the students used the internet for health purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] The study by Carroll students cited UpToDate, Google and Wikipedia were most cited resources by medical students for highly for their accessibility, understandability, and usefulness. [18] There is need to train students for fruitful use of internet.…”
Section: Discussionmentioning
confidence: 99%
“…Focus group findings from their study suggested potential reasons for these source usage patterns related to students' familiarity with Google and their inability to assess the relative efficacy of online decision-support resources [36]. More recent studies have shown similar findings, with Google, Wikipedia, and social media being the information-seeking resources most frequently used by contemporary medical students, whereas online journals, scholarly databases, and medical texts are accessed relatively infrequently [37][38][39]. Features such as ease of use and efficiency of access appear to heavily influence today's medical students' choices of such resources [39][40][41].…”
Section: % (3)mentioning
confidence: 97%